2016
DOI: 10.1097/pas.0000000000000606
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Loss of PMS2 Immunohistochemical Expression is Frequently Caused by Heterogenous MLH1 Promoter Hypermethylation in Lynch Syndrome Screening for Endometrial Cancer Patients

Abstract: Lynch syndrome (LS) is an autosomal-dominant inherited disorder mainly caused by a germline mutation in the DNA mismatch repair (MMR) genes (MLH1, MSH2, MSH6, and PMS2) and is associated with increased risk for various cancers, particularly colorectal cancer and endometrial cancer (EC). Women with LS account for 2% to 6% of EC patients; it is clinically important to identify LS in such individuals for predicting and/or preventing additional LS-associated cancers. PMS2 germline mutation (PMS2-LS) is the rarest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 37 publications
1
42
0
1
Order By: Relevance
“…79 In addition, MSH6 deficient EC can be microsatellite low or stable. 80 That said, IHC does enable a more targeted application of MLH1 promoter Heterogeneity: I 2 = 79%, τ 2 = 1.0813, p < 0.01 Egoavil et al 36 Frolova et al 15 Watkins et al 73 Najdawi et al 69 Backes et al 26 Buchanan et al 29 Kato et al 45 Chadwick et al 32 Goodfellow et al 40 Mills et al 53 Batte et al 14 Mas-Moya et al 17 Rubio et al 60 Hampel et al 41 Yoon et al 63 Hartnett et al 42 Dillon et al 13 Moline et al 54 Ferguson et al 37 Leenen et al 47 Lin et al 49 Rabban et al 18 Lu et al 50 hypermethylation testing, given that it need only be applied to MLH1 deficient tumors. In addition, germline analysis could be limited to the gene(s) that corresponds to the protein lost; this has potential cost saving implications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…79 In addition, MSH6 deficient EC can be microsatellite low or stable. 80 That said, IHC does enable a more targeted application of MLH1 promoter Heterogeneity: I 2 = 79%, τ 2 = 1.0813, p < 0.01 Egoavil et al 36 Frolova et al 15 Watkins et al 73 Najdawi et al 69 Backes et al 26 Buchanan et al 29 Kato et al 45 Chadwick et al 32 Goodfellow et al 40 Mills et al 53 Batte et al 14 Mas-Moya et al 17 Rubio et al 60 Hampel et al 41 Yoon et al 63 Hartnett et al 42 Dillon et al 13 Moline et al 54 Ferguson et al 37 Leenen et al 47 Lin et al 49 Rabban et al 18 Lu et al 50 hypermethylation testing, given that it need only be applied to MLH1 deficient tumors. In addition, germline analysis could be limited to the gene(s) that corresponds to the protein lost; this has potential cost saving implications.…”
Section: Discussionmentioning
confidence: 99%
“…In total, 14,770 tumors underwent tumor-based triage with IHC (n = 10,460) and/or MSI (n = 4310). Concurrent testing with both IHC and MSI was sufficiently reported in ten studies 16,27 Heterogeneity: I 2 = 85%, τ 2 = 0.2427, p < 0.01 González et al 39 Yoon et al 63 Riggi et al 58 Rubio et al 60 Ferguson et al 37 Najdawi et al 69 Long et al 67 Batte et al 14 Hartnett et al 42 Djordjevic et al 35 Backes et al 26 Watkins et al 73 Frolova et al 15 Egoavil et al 36 Mas-Moya et al 17 Bruegl et al 28 Resnick et al 57 Mills et al 53 Buchanan et al 29 Joehlin-Price et al 44 Goodfellow et al 40 Hampel et al 41 Dillon et al 13 Kato et al 45 Cossio et al 34 Woo et al 72 Lin et al 49 Pecorino et al 56 Kost et al 66 Matthews et al 51 Chu et al 68 Ring et al 71 Garg et al 38 Lu et al 50 Walsh et al 62 Rabban et al 18 Leenen et al 47 Sugawara et al 61 Tan et al 65 Moline et al 54 Lee et al 46 Berends et al 27 (n = 5594) all...…”
Section: Germline Analysismentioning
confidence: 99%
“…As detection of PMS2 germline mutations is problematic, this may result in patients being labelled as ‘Lynch‐like’, with implications for future surveillance . A recent study suggested that some cases of isolated PMS2 loss result from MLH1 promoter methylation and are sporadic rather than likely LS; they therefore recommended MLH1 promoter methylation testing in all cases of isolated PMS2 loss …”
mentioning
confidence: 99%
“…Prompted by this study, we performed an audit of cases showing isolated PMS2 loss at our respective institutions. Isolated PMS2 loss was seen in 16 of 1656 (1%) EC cases in one institution (A) and seven of 137 (5%) in the other (B) ( p = 0.0011).…”
mentioning
confidence: 99%
“…Immunohistochemistry-based approach helps identifying tumors exhibiting microsatellite instability when staining is negative for MLH1, PMS2, MSH2 and/or MSH6 antibodies [ 36 ]. In this setting, immunohistochemistry is recommended as a screening method for Lynch syndrome among patients with endometrial cancer [ 37 ]. Using immunohistochemistry assay, BRIP1 expression was observed to be reduced in cervical adenocarcinoma compared with normal cervix tissue and was correlated with unfavorable outcome including lymph node metastases [ 38 ].…”
Section: Discussionmentioning
confidence: 99%